Non-invasive fractional flow reserve (FFRCT) in the evaluation of acute chest pain – Concepts and first experiences. Issue 138 (May 2021) - Fischer, Andreas M.; van Assen, Marly; Schoepf, U. Joseph; Matuskowitz, Andrew J.; Varga-Szemes, Akos; Golden, Joseph W.; Giovagnoli, Dante A.; Tesche, Christian; Bayer, Richard R.
Highlights: CT derived FFR does not yet possess robust data for use within the acute chest pain population presenting to the Emergency Department. Patients presenting to the ED with acute chest pain undergoing CCTA with CT derived FFR, in which FFRCT is >0.8, results in low rates of MACE at 30 days. A standardized approach for integrating FFRCT into routine clinical practice is needed to ensure uniform application in medical decision making. Abstract: Objective: To evaluate 30 day rate of major adverse cardiac events (MACE) utilizing cCTA and FFRCT for evaluation of patients presenting to the Emergency Department (ED) with acute chest pain. Materials and methods: Patients between the ages of 18–95 years who underwent clinically indicated cCTA and FFRCT in the evaluation of acute chest pain in the emergency department were retrospectively evaluated for 30 day MACE, repeat presentation/admission for chest pain, revascularization, and additional testing. Results: A total of 59 patients underwent CCTA and subsequent FFRCT for the evaluation of acute chest pain in the ED over the enrollment period. 32 out of 59 patients (54 %) had negative FFRCT (>0.80) out of whom 18 patients (55 %) were discharged from the ED. Out of the 32 patients without functionally significant CAD by FFRCT, 32 patients (100 %) underwent no revascularization and 32 patients (100 %) had no MACE at the 30-day follow-up period. Conclusion: In this limited retrospective study, patients presenting to the ED with acute chest pain and with CCTA with subsequent FFRCT of >0.8 had no MACE at 30 days; however, for many of these patients results were not available at time of clinical decision making by the ED physician.